Integração espacial dos mercados exportadores de mel natural no Brasil: Abordagem utilizando cointegração com Threshold - Costa Junior, Manoel Pedro da (2012)
This study investigated the process of cointegration space between the main markets Brazilian exporters of natural honey Rio Grande do Sul, Santa Catarina, Piauí, Ceará and São Paulo. Secondary data obtained directly from the database of the Ministério de Desenvolvimento, Indústria e Comércio Exterior, comprising the time series between January 2002 and July 2011. To investigate the relationship between the markets mentioned above, was made use of a methodology based on the premises of the Law of One Price- LPU and modeling that considers the presence of transaction costs. The results indicate that despite the confirmation of the existence of markets cointegration Brazilian exporting natural honey, the LPU has not been fully confirmed, since it is rejecting the null hypothesis of perfect integration space between the markets. The weak exogeneity test indicates that the market for natural honey of Rio Grande do Sul acts asthe central market pricing. There is the presence of transaction costs between almost allspatially separated markets, because, according to the results from the modelingthreshold, rejected the null hypothesis of linear and symmetric adjustment between markets investigated.